Loss of Sphingosine Kinase Alters Life History Traits and Locomotor Function in Caenorhabditis elegans - Chan, Jason P.; Brown, Jaylene; Hark, Brandon; Nolan, Abby; Servello, Dustin; Hrobuchak, Hannah; Staab, Trisha A. (Frontiers in Genetics, 2017)
Sphingolipid metabolism is important to balance the abundance of bioactive lipid molecules involved in cell signaling, neuronal function, and survival. Specifically, the sphingolipid sphingosine mediates cell death signaling, whereas its phosphorylated form, sphingosine-1-phosphate (S1P), mediates cell survival signaling. The enzyme sphingosine kinase produces S1P, and the activity of sphingosine kinase impacts the ability of cells to survive under stress and challenges. To examine the influence of sphingolipid metabolism, particularly enzymes regulating sphingosine and S1P, in mediating aging, neuronal function and stress response, we examined life history traits, locomotor capacities and heat stress responses of young and old animals using the model organism Caenorhabditis elegans. We found that C. elegans sphk-1 mutants, which lack sphingosine kinase, had shorter lifespans, reduced brood sizes, and smaller body sizes compared to wild type animals. By analyzing a panel of young and old animals with genetic mutations in the sphingolipid signaling pathway, we showed that aged sphk-1 mutants exhibited a greater decline in neuromuscular function and locomotor behavior. In addition, aged animals lacking sphk-1 were more susceptible to death induced by acute and prolonged heat exposure. On the other hand, older animals with loss of function mutations in ceramide synthase (hyl-1), which converts sphingosine to ceramide, showed improved neuromuscular function and stress response with age. This phenotype was dependent on sphk-1. Together, our data show that loss of sphingosine kinase contributes to poor animal health span, suggesting that sphingolipid signaling may be important for healthy neuronal function and animal stress response during aging.□